Impacts of freshwater aquaculture on fish communities: A whole‐ecosystem experimental approach. (7th March 2019) - Rennie, Michael D.; Kennedy, Patrick J.; Mills, Kenneth H.; Rodgers, Chandra M.C.; Charles, Colin; Hrenchuk, Lee E.; Chalanchuk, Sandra; Blanchfield, Paul J.; Paterson, Michael J.; Podemski, Cheryl L.
Abstract: Aquaculture is a growing global industry; freshwater aquaculture has significant potential for expansion in Canada, but growth of the freshwater sector has been slow due to concerns over potential environmental impacts and a lack of information on potential impacts to native fish communities. To provide guidelines and target variables for evaluating aquaculture impacts on freshwater fish communities, we operated an experimental aquaculture farm as a whole‐lake experiment where 10, 000 rainbow trout ( Oncorhynchus mykiss ) were raised annually from 2003 to 2007. Impacts were assessed using up to 8 years of pre‐impact and 8–10 years of post‐impact data. Prey fish abundance increased dramatically during aquaculture but declined sharply following the experiment. High abundance of littoral minnows in autumn was not observed during spring and, combined with size distribution data, suggests high overwinter mortality of adult minnows. White sucker ( Catostomus commersonii ) abundance and body condition declined during and after aquaculture, with evidence of overwinter juvenile recruitment failure in the last 2 years of operation, although size‐at‐age increased. The adult abundance of lake trout ( Salvelinus namaycush ) doubled during aquaculture, due to a combination of (a) increased growth rates of young trout and (b) earlier age and larger sizes at maturation. Within 2 years following aquaculture, lake trout abundance declined by nearly 50% to background levels, suggesting a large increase in lake trout mortality once operations ceased. These changes were not observed in nearby reference lakes. While aquaculture appeared to benefit some species (slimy sculpin [ Cottus cognatus ], minnows, lake trout), prolonged declines in white sucker abundance and condition and continued depression of Mysis densities and optimal oxythermal habitat availability nearly a decade following operations suggest potentially long‐term impacts at this magnitude. Importantly, this experiment highlights important indicator species and life history traits for monitoring of freshwater aquaculture impacts on native fish communities.